The Effectiveness of Animated Story Videos in Discovery Learning for Improving Fifth-Grade Students' Ability to Identify Moral Values in Short Stories - Elsalama, Hilda Firdaus; Retnosari, Ira Eko (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
This study was motivated by the fact that Indonesian language instruction at SDN Keboananom Gedangan is still dominated by conventional methods and makes insufficient use of engaging learning media, resulting in students being less active and experiencing difficulties in identifying moral values in short stories. Therefore, an innovative learning model suited to the characteristics of elementary school students is needed. The Discovery Learning model emphasizes students’ active engagement in independently discovering concepts, while animated story videos help present material visually and audibly to make it easier to understand. This study aims to describe the effectiveness of using the Discovery Learning model supported by animated story videos on fifth-grade elementary students’ ability to identify moral values in short stories. This study employs a quantitative approach using a quasi-experimental design and a Non-Equivalent Control Group Design. The study population consists of all fifth-grade students at SDN Keboananom Gedangan, with a purposive sampling technique. Data collection utilized a test, while data analysis included normality tests, homogeneity tests, and hypothesis testing using the t-test. The results of the analysis show a p-value of 0.013 < 0.05, so it can be concluded that the Discovery Learning model supplemented with animated story videos is effective in improving fifth-grade students’ ability to identify the moral values in short stories